2010
DOI: 10.1517/14728214.2010.480973
|View full text |Cite
|
Sign up to set email alerts
|

The future is today: emerging drugs for the treatment of erectile dysfunction

Abstract: Erectile Dysfunction (ED) is the most common male sexual dysfunction presented for treatment, and the most thoroughly studied sexual dysfunction in men. In the late 20th century, important discoveries were made regarding both the physiologic processes of penile erection and the pathophysiology of ED. These discoveries led to the commercial introduction of the phosphodiesterase type 5 inhibitors (PDE5I), a class of medications which now accounts for the largest segment of the ED market. While these drugs are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 83 publications
0
71
0
Order By: Relevance
“…Modulation of ventral striatal activation by the subjectively perceived sexual intensity of a stimulus has been described before (Walter et al, 2008a), and changes in activity of the ventral striatum have been reported in various contexts of a rewarding sexual stimulation (Hamann et al, 2004;Stark et al, 2005). Dopamine agonists have been shown to induce penile erection in animals and humans (Carson, 2007) and have been suggested as promising agents for the treatment of sexual dysfunction (Albersen et al, 2010). Dopamine agonists have further been related to hypersexuality in the treatment of Parkinson's disease (for review, see Voon et al, 2009).…”
Section: Activity Increases Of Subcortical Regions Under Bupropionmentioning
confidence: 98%
“…Modulation of ventral striatal activation by the subjectively perceived sexual intensity of a stimulus has been described before (Walter et al, 2008a), and changes in activity of the ventral striatum have been reported in various contexts of a rewarding sexual stimulation (Hamann et al, 2004;Stark et al, 2005). Dopamine agonists have been shown to induce penile erection in animals and humans (Carson, 2007) and have been suggested as promising agents for the treatment of sexual dysfunction (Albersen et al, 2010). Dopamine agonists have further been related to hypersexuality in the treatment of Parkinson's disease (for review, see Voon et al, 2009).…”
Section: Activity Increases Of Subcortical Regions Under Bupropionmentioning
confidence: 98%
“…For a more elaborate discussion, we refer the reader to references [13] and [14] . Penile erection is a complex neurovascular phenomenon under hormonal control.…”
Section: Physiologymentioning
confidence: 99%
“…Calmodulin in turn dissociates from myosin light chain kinase, thus inactivating it in turn leading to smooth muscle relaxation, and ultimately, to penile tumescence. Figure and legend adapted from Albersen et al [14] .…”
Section: Physiologymentioning
confidence: 99%
“…The discovery of the NO signaling pathway in penile tissue has led to a Association of lower urinary tract symptoms and erectile dysfunction H Orabi et al revolution in ED research and to the development of phosphodiesterase-5 (PDE5) inhibitors, which now constitute first-line therapy for men with ED. 13 In recent years, it has been recognized that reduced NO availability is linked to the development of prostate gland hyperplasia and the subsequent development of LUTS. As a logical result, there is an increasing interest in the NO pathway as a potential pharmacological target to treat male LUTS.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%